Liczba uczestników zgromadzenia i jej znaczenie prawne w obecnym i dawnym prawie o zgromadzeniach - Bartoszewicz, Michał (Wydawnictwo eBooki.com.pl, 2018)
The exercise of freedom of assembly may take different forms, but the objective meaning of the word ‘assembly’ must be subject to a number of conditions. It is certainly not mass attendance, but, on the other hand, it is not possible to consider one person’s speech as an assembly. The author of this article considers the number of three participants to be sufficient.The minimum number of participants of the public assembly was an element of the definition of the Law on Assemblies of 5 July 1990 determining the subject matter of regulation, which was not mentioned in the explanations contained in the previous acts. The question arises whether it is advisable to refer to the number of participants of the meeting in the statutory definition or in other provisions concerning the scope of interference with the freedom of assembly. Certainly, the checking of the number of participants is burdened with several difficulties. The author considers whether, despite the important objections to this definition criterion, it could not, in a more prudent interpretation, fulfill a positive role. The Constitutional Tribunal in its judgment of 18 September 2014, K 44/12, ruled on the unconstitutionality of including the number of persons in the definition of the assembly, using the argument of the lack of regulation and legal protection of groupings connecting less than fifteen people. This feature is no longer included in the definition contained in the new act.
Keywords: the number of participants; notification of the planned assembly; assembly; the freedom of assembly